Peningkatan Literasi Pengelolaan Sampah Berbasis Masyarakat Bagi Kelompok Sadar Lingkungan - Adil Mubarak; Lince Magriasti; Rizki Syafril (Faculty of Social Science, Universitas Negeri Padang, 2022)
The issue of environmental pollution due to waste is a complicated homework for stakeholders. Waste management efforts by transporting waste to the final disposal site (TPA) carried out by the Environmental Awareness Group (pokdarling) are currently unable to solve the problem. In fact, the two units of garbage hauling carts that operate are unable to transport waste to an integrated landfill, so that piles of garbage have sprung up along the nagari road and along the nagari coast. This research through the Community Partnership Program (PKM) aims to overcome the waste problem through increasing literacy. waste management to environmental awareness groups (pokdarling) Kampung Padang Nagari Air Bangis. Literacy improvement is carried out through a workshop method in the form of training and assistance in technology transfer based on participatory principles by emphasizing the principle of partner participation to achieve the goals and objectives that have been determined. The results obtained in this activity are the increased literacy of the target group and the birth of a community-based waste management design with a waste management model through the Waste Bank, Composting and Maggot Cultivation.